Combining ability for seed yield and its component traits in castor (Ricinus communis L.): Combining ability for seed yield and its component traits in castor (Ricinus communis L.) - R B MADARIYA; M S CHAUDHARI; K L DOBARIYA (Journal of Oilseeds Research, 2020)
Combining ability analysis was carried out using five pistillate lines as female and 13 monoecious lines as male for seed yield and component traits in castor. The result indicated that both gca and sca variances were important in the expression of all the traits. Non-additive gene action was predominant for seed yield and oil content, while additive gene action was more important in the expression of length of main spike, number of capsules on main spike, number of effective spikes/plant and 100-seed weight. Three pistillate lines, JP-96, JP-106 and SKP-84 and five male lines, JI454, JI-455, JI-456 and JI-457 were good general combiners for yield and its contributing traits.